The Influence of ESG on Dividend Policy in Indonesia Companies - Filman, Fikri Aulian; Rahmayanti, Dewi (AFEBI Economic and Finance Review, 2023)
This research aims to examine the influence of Environmental, Social, and Governance (ESG) disclosure on Dividend Policy. The population in this study consists of all companies listed on the Bursa Efek Indonesia from 2017-2021. The variabel used in this research are Dividend Policy as a dependent variable; Environmental, Social, and Governance as independent variable; and company size and levrage as control variable. The sampling technique employed is purposive sampling, resulting in a total of 130 data samples. The analysis methods used include classical assumption tests, multiple linear regression, and hypothesis testing. The research finding indicate that Environmental, Social, and Governance have a positive influence on Dividend Policy. The control variable, Company Size, have a positive impact on Dividend Policy, while Leverage has a negative effect on Dividend Policy.